Cave to mill: improving value of caving operations - Moss, A; Klein, B; Nadolski, S (Caving 2018: Proceedings of the Fourth International Symposium on Block and Sublevel Caving, 2018)
Forecasts indicate that there will be an increase in copper production from underground operations over the coming decades as available resources trend deeper. It is anticipated that a significant portion of this production will be from caving operations. Caving has a very different risk profile to open pit mining and other underground methods, with one of the critical areas being run-of-mine (ROM) grades that are delivered to the mill. Though caving can match pits in terms of operating cost per tonne, it suffers from limited grade selectivity with ROM grades trending toward the orebody average due to the consequences of mixing in cave columns. Research and subsequent operational trials have demonstrated that bulk sorting can manage this lack of selectivity by ‘pre-concentrating’ the ROM ore, providing the mill with a more consistent and higher grade feed. The paper describes the ‘cave to mill’ concept where the objective is to provide consistent feed (tonnes and grade) to the flotation circuit. This is done in three stages. The first stage is better characterisation of the material reporting to drawpoints. Secondly, measurement of the variation in metal content that is delivered from drawpoints through the use of scanners and sensors at various points in the ore flow system. Finally, bulk sorting systems offer flexibility and control by allowing classification of waste, low-grade and mill-grade streams in real time. The potential for bulk sorting is dependent on the heterogeneity of the ore and the ability of sensors to detect the heterogeneity. The broad technical requirements for each stage are discussed together with the associated business case.
Keywords: block cave mining